Soy bean meal and HP 300 in blue fox (Alopex lagopus) feed during growing-furring period - Koskinen, Nita; Pylkkö, Päivi; Sepponen, Juhani; Rekilä, Teppo (fi, 2006)
Blue foxes fed by Soy bean meal (SBM) and Hamlet Protein® HP 300 (HP 300) diets maintained good health during experiment and no faecal problems appeared. Weight gaining and skin properties were normal in both groups. Our results indicate that HP300 is a potential alternative plantprotein source in blue fox diets. The digestibility values of protein, fat and carbohydratres as informed by the manufacturer were quite high (studied with pigs). If the values are lower in furbearing animals than assumed the calculated metabolisable energy of HP300 is lower. In diet formulation the digestibility values by manufacturer were used. Further research is needed to determine the digestibility values of HP300 in blue fox and mink. v